Livestock production in the subhumid zone of West Africa : A regional review - International Livestock Centre for Africa (International Livestock Centre for Africa, 1979)
Description of geographical aspects of the Subhumid Zone of West Africa and economic and sociological aspects of the Fulani ethnic group, w. emphasis on fodder resources, range management, livestock raising, livestock management, and animal diseases, w. analysis of land use & land development strategies, and directions for future research.